The Living with Dysarthria group for post‐stroke dysarthria: the participant voice. Issue 4 (17th April 2013) - Mackenzie, C.; Kelly, S.; Paton, G.; Brady, M.; Muir, M.
Abstract Background The Living with Dysarthria group programme, devised for people with post‐stroke dysarthia and family members, was piloted twice. Feedback from those who experience an intervention contributes to the evaluation of speech and language therapy programmes, giving the participant view of the intervention's value and guiding further developments. Research Question What feedback do participants in the Living with Dysarthria programme provide, informing on its perceived usefulness and guiding its future development? Methods & Procedures Nine people with chronic dysarthria following stroke and four family members who completed the Living with Dysarthria programme all contributed to Focus Group (FG) discussion, transcribed and thematically analysed, and completed an Anonymous Questionnaire Evaluation (AQE), comprising closed statements and open questions. An anonymous descriptive adjective selection task (ADAST) was also used. Outcomes & Results The varied forms of feedback provided complementary information. Thematic analysis of FG data and AQE open question responses were configured around programme benefits, programme structure and content, and programme practicalities. Benefits associated with participation included learning and insight, being supported by peers and professionals, and improved speech and confidence. These are consistent with the main programme elements of education, support and speech practice. All activities were seen as relevant and positively received. Flexibility, recognition of and catering to individual needs were valued characteristics. The community location was approved by all. Most participants thought the format of eight weekly sessions of 2 h was appropriate. Responses to AQE closed statements provided almost unanimous confirmation of the very positive feedback conveyed in FG discussions. The main response to suggested improvements in AQEs was that the number of sessions should be increased. Feedback indicated that for a few individuals there was negative reaction to some facts about stroke, home practice tasks were difficult to complete, the person with dysarthria/family member pair may not be the optimum combination for paired practice activities and pre‐programme information should be extended. The ADAST showed that the programme was enjoyable, interesting, stimulating and useful. Conclusions & Implications Participant feedback indicates that group therapy, with family member participation, is a valid form of management for chronic post‐stroke dysarthria. Education, peer and professional support, and speech practice are confirmed as relevant programme components. Consistent majority opinions were communicated in different situations and via varied mediums. Some individuals expressed views relevant to their own needs, and these responses also inform future implementation of the Living with Dysarthria programme.